1993
DOI: 10.1063/1.464907
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio investigation of potential-energy surfaces involved in the photophysics of benzene and pyrazine

Abstract: Potential-energy surfaces of the lowest singlet and triplet excited states of benzene and pyrazine have been calculated using complete-active-space self-consistent-field and multireference configuration interaction (MRCI) techniques. We have focused our attention on the saddle points and surface intersections associated with the reaction path to a biradical form called prefulvene. The barrier heights separating the prefulvenic minimum from the minimum of the planar aromatic form on the Z-T* excited singlet sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 62 publications
9
91
0
Order By: Relevance
“…This is also in agreement with theoretical results. 43 Consequently, for BZA and ACP, each with a low-lying S 1 (nπ*) state, their rapid electronic relaxation rates are much greater than that of benzene because (i) the isomerization pathway to the prefulvenic form has no barrier, as in the case of pyrazine, or (ii) because electronic relaxation to S 1 (nπ*) followed by rapid ISC to triplet states becomes important. Since T 1 (nπ*) f S 0 phosphorescence of BZA was observed upon S 2 (ππ*) excitation, 83 it was suggested that a S 2 (ππ*)-T 1 (nπ*) relaxation channel may exist prior to phosphorescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also in agreement with theoretical results. 43 Consequently, for BZA and ACP, each with a low-lying S 1 (nπ*) state, their rapid electronic relaxation rates are much greater than that of benzene because (i) the isomerization pathway to the prefulvenic form has no barrier, as in the case of pyrazine, or (ii) because electronic relaxation to S 1 (nπ*) followed by rapid ISC to triplet states becomes important. Since T 1 (nπ*) f S 0 phosphorescence of BZA was observed upon S 2 (ππ*) excitation, 83 it was suggested that a S 2 (ππ*)-T 1 (nπ*) relaxation channel may exist prior to phosphorescence.…”
Section: Discussionmentioning
confidence: 99%
“…In direct S 2 (ππ*) excitation, it was assumed that the S 2 (ππ*)-S 1 (nπ*) IC rate is much more rapid than the S 1 (nπ*) decay rate. 33 Theoretical calculations on pyrazine 43 indicate that the S 1 (nπ*) PES intersects the S 2 (ππ*) surface near the S 2 minimum and, via the ν 10a (B 1g ) vibrational mode, form a conical intersection. 82 Theoretical results 43 also indicate that the pyrazine S 2 (ππ*) surface exhibits a behavior similar to that of the benzene S 1 (ππ*) surface, the latter correlating with the ground state of the prefulvenic form and, therefore, there exists no isomerization barrier in the reaction path.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we describe a method which enables the a priori selection of these important coordinates for a photochemical reaction using an analytic simultaneous representation of both ground and excited states correct to second order in the energy ͑i.e., using analytic gradients and second derivatives of the energy difference [8][9][10] ͒. The efficacy of the method will be illustrated using the channel 3 photochemistry of benzene, 11,12 where the energy difference was analyzed at the S 0 minimum.…”
Section: Introductionmentioning
confidence: 99%
“…The first two excited singlet states, S 1 and S 2 , resulting from promotion of either a non-bonding or a valence π electron to an anti-bonding π * orbital, correspond to diabatic states with 1 B 3u and 1 B 2u symmetries, respectively. [22] These diabatic states are strongly coupled by the 10a bending mode of b 1u symmetry. [23] Because of this strong coupling, the S 2 spectrum is very diffuse, [24,25] and IC occurs in only 22 fs.…”
Section: Introductionmentioning
confidence: 99%